KEBIJAKAN KRIMINAL TERHADAP TINDAK PIDANA INTIMIDASI DI INTERNET (CYBERBULLYING) SEBAGAI KEJAHATAN MAYANTARA (CYBERCRIME) - Agusta Ridha Minin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2018)
The crime of cyber crime is one of the greatest crimes that occurred during this century. The manifestations of this crime vary depending on the development of information and technology, one of which is cyber bullying. Intimidation to victims through cyber is done indirectly. Government policy in minimizing the crime of intimidation through social networking, internet and other electronic media is regulated in Law no. 11 Year 2008 on Information and Electronic Transactions. In addition to special regulations in the law, the government also accommodates the provisions of cyber crime in the Draft Penal Code. On the basis of the issues examined in the regulation of positive criminal law on cyber bullying as one form of cybercrime. And, criminal policy in Indonesia as an effort to overcome cyber bullying crime in the future.